Capsule Endoscopy for Obscure Gastrointestinal Bleeding in Patients with Comorbid Rheumatic Diseases. (6th July 2014) - Shahidi, Neal; Ou, George; Tong, Jessica; Kwok, Ricky; Galorport, Cherry; Law, Joanna K.; Enns, Robert
Abstract : Background and Aim . We evaluated the association between patients with rheumatic diseases (RD) suffering from obscure gastrointestinal bleeding (OGIB) and positive capsule endoscopy (CE) findings. Methods . All CE procedures performed on patients with RD and OGIB were assessed from a large database at St. Paul's Hospital (Vancouver, BC, Canada) between December 2001 and April 2011. A positive finding on CE was defined as any pathology, including ulcers/erosions, vascular lesions, and mass lesions, perceived to be the source of bleeding. Results . Of the 1133 CEs performed, 41 (4%) complete CEs were for OGIB in patients with RD. Of these, 54% presented with overt bleeding. Mean age was 66 years. Positive findings were seen in 61% of patients. Ulcerations/erosions (36%) and vascular lesions (36%) were the most common findings. Significant differences between the RD versus non-RD populations included: inpatient status, nonsteroidal anti-inflammatory drug (NSAIDs) use, oral steroid use, and mean Charlson index score (allP ≤ 0.008 ). Similar nonsignificant trends were seen between positive and negative CEs among the RD population. Conclusions . The correlation between RD and positive CE findings is likely influenced by ongoing anti-inflammatory drug use, poorer health status, and a predisposition for angiodysplastic lesions.